STIMULASI KEMAMPUAN KOGNITIF MELALUI MODEL PEMBELAJARAN ASYIK ANAK DIDIK KELAS B TK NEGERI 2 BUTON - Suarti; Sri Watini (Melati Institute, 2023)
This journal aims to present one of the learning models, namely ASYIK (Active, Social, Sure & Confident, Innovative, Creative) to improve students' cognitive abilities at TK Negeri 2 Buton. This ASYIK learning model is expected to increase students' enthusiasm in the learning process because it does not only prioritize memorizing learning concepts but in the process involves students to be active, social, innovative, and creative. This learning model is very suitable for use at the kindergarten level because it holds the principle of playing while learning. Students will be more cognitively improved if learning is presented with students playing an active role in the learning process. The method used in this research is descriptive qualitative. With a qualitative approach, the author can understand, observe, analyze, and examine more accurately regarding the stimulation of children's cognitive abilities through the ASYIK learning model.